The role of green tea intake in thromboprophylaxis of venous thromboembolism in patients with cancer - Yao, Qihuan; Qiao, Hongwei; Cheng, Yi; Du, He; Zhang, Yanbin; Luo, Yong; Wang, Hongwei; Liu, Song; Xu, Mei; Xiong, Wei (Frontiers in Nutrition, 2024)
Background Green tea intake has been reported to improve the clinical outcomes of patients with cardiovascular diseases or cancer. It may have a certain role in the development of venous thromboembolism (VTE) among cancer patients. The current study aimed to address this issue, which has been understudied. Methods We carried out a retrospective study to explore the role of green tea intake in cancer patients. Patients with and without green tea intake were enrolled in a 1:1 ratio by using propensity scoring matching. The primary and secondary outcomes were VTE development and mortality 1 year after cancer diagnosis, respectively. Results The cancer patients with green tea intake (n = 425) had less VTE development (10 [2.4%] vs. 23 [5.4%], p = 0.021), VTE-related death (7 [1.6%] vs. 18 [4.2%], p = 0.026), and fatal pulmonary embolism (PE) (3 [0.7%] vs. 12 [2.8%], p = 0.019), compared with those without green tea intake (n = 425). No intake of green tea was correlated with an increase in VTE development (multivariate hazard ratio (HR) 1.758 [1.476–2.040], p < 0.001) and VTE-related mortality (HR 1.618 [1.242–1.994], p = 0.001), compared with green tea intake. Patients with green tea intake less than 525 mL per day had increased VTE development (area under the curve (AUC) 0.888 [0.829–0.947], p < 0.001; HR1.737 [1.286–2.188], p = 0.001) and VTE-related mortality (AUC 0.887 [0.819–0.954], p < 0.001; HR 1.561 [1.232–1.890], p = 0.016) than those with green tea intake more than 525 mL per day. Green tea intake caused a decrease in platelet (p < 0.001) instead of D-dimer (p = 0.297). The all-cause mortality rates were similar between green tea (39 [9.2%]) and non-green tea (48 [11.3%]) intake groups (p = 0.308), whereas the VTE-related mortality rate in the green tea intake group (7 [1.6%]) was lower than that of the non-green tea intake group (18 [4.2%]) (p = 0.026). The incidences of adverse events were similar between the green tea and non-green tea intake groups. Conclusion In conclusion, the current study suggests that green tea intake reduces VTE development and VTE-related mortality in cancer patients, most likely through antiplatelet mechanisms. Drinking green tea provides the efficacy of thromboprophylaxis for cancer patients.